2014
DOI: 10.1093/humrep/deu054
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional ultrasonography in the diagnosis of deep endometriosis

Abstract: This study was supported in part by the Regione Autonoma della Sardegna (project code CPR-24750).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 30 publications
6
59
2
1
Order By: Relevance
“…For MRI in the detection of DIE in the uterosacral ligaments, pooled sensitivity was 0.70 (95% CI, 0.55-0.82), specificity was 0.93 (95% CI, 0.87-0.97), LR+ was 10.4 (95% CI, 5.1-21.2), . For TVS in the detection of DIE in the uterosacral ligaments, pooled sensitivity was 0.67 (95% CI, specificity was 0.86 (95% CI, LR+ was 4.8 (95% CI,, LRwas 0.38 (95% CI,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Confidence intervals of pooled sensitivities, specificities and DOR were wide for both techniques in all the locations considered.…”
mentioning
confidence: 99%
“…For MRI in the detection of DIE in the uterosacral ligaments, pooled sensitivity was 0.70 (95% CI, 0.55-0.82), specificity was 0.93 (95% CI, 0.87-0.97), LR+ was 10.4 (95% CI, 5.1-21.2), . For TVS in the detection of DIE in the uterosacral ligaments, pooled sensitivity was 0.67 (95% CI, specificity was 0.86 (95% CI, LR+ was 4.8 (95% CI,, LRwas 0.38 (95% CI,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Confidence intervals of pooled sensitivities, specificities and DOR were wide for both techniques in all the locations considered.…”
mentioning
confidence: 99%
“…There is mounting literature indicating that transvaginal sonography can detect deep infiltrating endometriosis, using extended techniques, including introduction of gel in the vagina and rectum to enhance the visualization of the cul-de-sac, wall of the rectosigmoid, rectovaginal septum, and posterior compartment of the pelvis. [1][2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19] Most patients in these prior studies were preselected with a high suspicion of endometriosis. [2][3][4][5][6][7][8][9] Our study differed in that we routinely evaluate the rectosigmoid and cul-de-sac of all patients undergoing pelvic sonography, including evaluating the mobility of the uterus within the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] These lesions are typically identified by using enhanced patient preparation techniques, including emptying the bowel with a bowel preparation, introducing gel into the upper vagina for additional distention, and placing gel in the rectum to better visualize the bowel wall. [2][3][4][5][6] Expanded sonography using a "tenderness-guided" examination, evaluation of the mobility of the uterus within the cul-de-sac by manual displacement, as well as adjunctive 3-dimensional imaging techniques may enhance the detection of bowel wall lesions. [7][8][9] In this study, we evaluated the cul-de-sac and bowel wall of all patients referred for pelvic sonography to determine whether we could identify deep infiltrating endometriosis of the surrounding bowel wall without the use a bowel preparation, vaginal or rectal gel application, or specific 3-dimensional imaging of the pelvic floor.…”
mentioning
confidence: 99%
“…Recently, Guerriero et al investigated the role of 3D USG in DIE. They concluded that while the sensitivity and specificity of 2D USG and 3D USG were not statistically different for rectosigmoid involvement, 3D USG reduced false negatives by 47-75 % and was significantly more specific in non-intestinal locations, namely the uterosacral ligaments, rectovaginal septum, and vaginal fornix [22].…”
Section: Benign Gynecologymentioning
confidence: 99%